Coupled Dynamic Modeling of Rolls Model and Metal Model for Four High Mill Based on Strip Crown Control - Sun, Jianliang; Peng, Yan; Liu, Hongmin (Chinese journal of mechanical engineering, 2013)
The crown is a key quality index of strip and plate, the rolling mill system is a complex nonlinear system, the strip qualities are directly affected by the dynamic characteristics of the rolling mil. At present, the studies about the dynamic modeling of the rolling mill system mainly focus on the dynamic simulation for the strip thickness control system, the dynamic characteristics of the strip along the width direction and that of the rolls along axial direction are not considered. In order to study the dynamic changes of strip crown in the roiling process, the dynamic simulation model based on strip crown control is established. The work roll and backup roll are considered as elastic continuous bodies and the work roll and backup roll are joined by a Winkler elastic layer. The rolls are considered as double freely supported beams. The change rate of roll gap is taken into consideration in the metal deformation, based on the principle of dynamic conservation of material flow, the two dimensional dynamic model of metal is established. The model of metal deformation provides exciting force for the rolls dynamic model, and the roils dynamic model and metal deformation model couple together. Then, based on the two models, the dynamic model of rolling mill system based on strip crown control is established. The Newmark-13 method is used to solve the problem, and the dynamic changes of these parameters are obtained as follows： （1） The bending of work roll and backup roll changes with time; （2） The strip crown changes with time; （3） The distribution of rolling force changes with time. Take some cold tandem rolling mill as subject investigated, simulation results and the comparisons with experimental results show that the dynamic model built is rational and correct. The proposed research provides effective theory for optimization of device and technological parameters and development of new technology, plays an important role to improve the strip control precision and strip shape quality.